Sedative effect of an alcoholic extract of Valeriana sp in tilapia fingerlings (Oreochromis niloticus) to reduce stress during simulated transport - Montañez Calero, Tessy (2022)
The aim of this study was to evaluate the sedative effect of three products: valerian extract (Valeriana officinalis), benzocaine and tricaine methanesulfonate (MS-222) on stress levels produced by a simulated transport model in tilapia fingerlings. In a first part, the sedative dose of the products was determined based on the clinical characteristics that indicate depression of the central nervous system. In the second part, sedation and subsequent simulated transport for 3 hours were performed. The fish were euthanized, and blood samples were taken from the tail vein to determine cortisol (ELISA) and glucose (portable glucometer) levels, haematological parameters and mortality. The optimal doses of sedation were 200, 35 and 75 mg/l, respectively, for valerian extract, benzocaine and MS-222. After 3 h of simulated transport, cortisol and glucose values were similar or higher compared to the non-sedated control group. The haematocrit did not present significant variation (p>0.05) in the group treated with valerian, while the other treated groups presented lower values than the control (p<0.05). All the treated groups presented low total protein values (p<0.05) and none of the groups presented mortality. It was concluded that, although it was possible to establish a state of sedation in tilapia fingerlings with specific doses of benzocaine, MS-222 and valerian extract, the doses were not sufficient to reduce stress during simulated transport for 3 h.